2017
DOI: 10.9734/air/2017/33423
|View full text |Cite
|
Sign up to set email alerts
|

Some Aspects of Nutrient, Antinutrient, Minerals and Sugars Contents of Thaumatococcus daniellii (Benn.) Seeds

Abstract: Thaumatococcus daniellii is an under-exploited, wild rhizomatous perennial herb from Africa that is classified as one of the non-timber forest products. The aril contains an intensely sweet and nontoxic protein used as sweetener in food and other related industries. This study evaluated the nutrient, antinutrient, minerals and sugars contents of T. daniellii seeds. The proximate analysis of the seeds in percent on dry basis revealed 9.18±0.04 ash, 10.52±0.10 moisture, 2.48±0.02 crude fat, 29.45±0.13 crude fibr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
(22 reference statements)
0
1
0
Order By: Relevance
“…Extensive studies have been conducted to determine the qualitative and quantitative phytochemical constituents of T. daniellii , with many studies confirming the presence of some compounds with biological importance ( Table 2 ). Previous studies by Elemo et al ( 1999 ), Elemo et al ( 2001 ), Oforibika et al ( 2017 ), and Oyeleke et al ( 2017 ) reported that the pericarp and seeds contain high content of phytic acid, tannins, saponins, and polyphenol. Tandemly, quantitative phytochemical analyses of extracts of fruit (pericarp and seeds), leaf, and root revealed the presence of alkaloids, tannins, saponins, flavonoids, phlobatannins, anthraquinones, phytate, phenol, steroids, and terpenoids in high quantities (Adeyemi et al, 2014 ; Ndukwe et al, 2014 ; Shalom et al, 2014 ; Adeogun et al, 2016 ; Oke et al, 2016 ; Oboh et al, 2016 ; Hamid et al, 2017 ; Ogoloma et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%
“…Extensive studies have been conducted to determine the qualitative and quantitative phytochemical constituents of T. daniellii , with many studies confirming the presence of some compounds with biological importance ( Table 2 ). Previous studies by Elemo et al ( 1999 ), Elemo et al ( 2001 ), Oforibika et al ( 2017 ), and Oyeleke et al ( 2017 ) reported that the pericarp and seeds contain high content of phytic acid, tannins, saponins, and polyphenol. Tandemly, quantitative phytochemical analyses of extracts of fruit (pericarp and seeds), leaf, and root revealed the presence of alkaloids, tannins, saponins, flavonoids, phlobatannins, anthraquinones, phytate, phenol, steroids, and terpenoids in high quantities (Adeyemi et al, 2014 ; Ndukwe et al, 2014 ; Shalom et al, 2014 ; Adeogun et al, 2016 ; Oke et al, 2016 ; Oboh et al, 2016 ; Hamid et al, 2017 ; Ogoloma et al, 2017 ).…”
Section: Introductionmentioning
confidence: 93%